ANALISIS PENGARUH INTERVENSI MANAJEMEN TERHADAP EFEKTIFITAS HUBUNGAN KOMITE AUDIT DAN AUDITOR EKSTERNAL DALAM AUDIT UMUM LAPORAN KEUANGAN PERUSAHAAN PUBLIK - Made Dudy Satyawan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2013)
This research discovery result is known that Management intervention has significant influences to the relation effectiveness, but the relation direction is on the sign contrary or positive to the first prediction. Positive response from the respondents tends to be based on the following consideration : 1) Reality condition of public company ownership structure in Indonesia is still dominated or concentrate on the company founder families, 2) there has not been existed clear separation between ownership and company control which is registered in BEI so that the company management exists on the owner control majority, 3) Agency theory is developed in the country where the stock market condition has been improved compared with Indonesia, and historically has different society cultural background.